Amaranthus viridis L. (Amaranthaceae) – a new alien species for Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The first record from Ukraine of an alien species Amaranthus viridis L. (city of Kerson) is reported (). The description of the species, its diagnostic characters, primary and secondary (synanthropic) distribution and main characteristics of the habitat are provided.
Keywords: Amaranthus viridis, Amaranthaceae, alien species, the first record from Ukraine, city of Kherson.